Creutzfeldt–Jakob Disease–Like Periodic Sharp Wave Complexes in Voltage-Gated Potassium Channel–Complex Antibodies Encephalitis: A Case Report. Issue 1 (February 2016) - Savard, Martin; Irani, Sarosh R.; Guillemette, Annie; Gosselin-Lefebvre, Stéphanie; Geschwind, Michael; Jansen, Gerard H.; Gould, Peter V.; Laforce, Robert
Abstract : Introduction: Voltage-gated potassium channel–complex antibodies (VGKC-cAbs) encephalitis, a treatable autoantibody encephalopathy, has been previously reported to clinically mimic sporadic Creutzfeldt–Jakob disease. Among available clinical clues to distinguish them, periodic sharp wave complexes, a typical finding in sporadic Creutzfeldt–Jakob disease, have never been reported in association with VGKC-cAbs encephalitis. Case Presentation: A 76-year-old man was transferred to a tertiary neurology center with a clinical history of 6-month weight loss, cognitive disturbance, and nonspecific generalized weakness. He had two seizures the month before transfer and then evolved to severe encephalopathy, requiring mechanical ventilation. Periodic sharp wave complexes every 1 to 2 seconds over slowed background were found on EEG, and MRI showed cerebellar and bifrontal cortical T2/FLAIR/DWI hypersignal without restricted diffusion on ADC mapping. Pancorporal positron emission tomography scan was negative. An immunotherapy trial did not improve the patient condition. Therefore, he died after life support withdrawal. Brain autopsy revealed mononuclear neocortex infiltrate without significant spongiosis, and the anti-VGKC test showed a seropositivity of 336 pmol/L (normal, 0–31), 3 month after the patient deceased. Conclusions: This is the first reported case of VGKC-cAbs encephalitis associated with periodic sharp wave complexes on EEG, which further confuse the differential diagnosis with sporadic Creutzfeldt–Jakob disease. However, the cortical DWI hypersignal without restriction seems to remain a way to discriminate these two entities appropriately, when present. These clues are of paramount importance because VGKC-cAbs encephalitis is a treatable disease.